Effect of textile waste on the mechanical properties of polymer concrete - João Marciano Laredo dos Reis (Materials Research, 2009)
The mechanical behavior of polymer concrete reinforced with textile trimming waste was investigated. Two series of polymer concrete formulations were studied, with different resin/sand (i.e. binder/fine aggregate) weight ratios. In each series, recycled textile chopped fibers at 1 and 2% of the total weight was used. Flexural and compressive tests were performed at room temperature and load vs. displacement curves were plotted up to failure. In the study, both the influence of fiber content and resin/sand weight ratio were considered relative to the behavior of polymer concrete reinforced with textile fibers. A decrease in properties was observed as function of textile fibers content. When specific properties were considered, this tendency was kept. However, higher textile fibers content lead to a smoother failure, unlike brittleness failure behavior of unreinforced polymer concrete.